Meningkatkan Niat Pembelian secara Online melalui Kualitas Website dan Kepercayaan - RABYN RAMDHANY, MOHAMMAD (Jurnal Ilmu Manajemen (JIM), 2019)
Competition in electronic commerce is closely related to the website. In an effort to win market competition, the quality of the website continues to be improved by increasing the diversity of features on its website. In addition, the rampant crime in electronic commerce requires electronic commerce sites to maintain consumer trust through a good reputation on the website. The website quality and trust can form an awareness in the consumer which gives rise to a good attitude that will lead to stronger online purchase intention. This research aims to determine the influence of website quality and trust on online purchase intention (study on OLX.co.id Site Visitors). The population in this study were OLX.co.id site visitors who had never made a purchase through the OLX.co.id site. The samples taken were 220 respondents using nonprobability sampling technique with a judgmental sampling and snowball sampling approach. Statistical analysis used is multiple linear regression analysis by using software PASW Statistic 18. According to the statistical data analysis show that the website quality has a positive and significant influence on online purchase intention. Trust has a positive and significant influence on online purchase intention. Keywords: electronic commerce; online purchase intention; trust; website features; website quality.